2006
DOI: 10.1179/oeh.2006.12.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Woodsmoke and Associated Respiratory Emergency Department Visits in Spokane, Washington

Abstract: Three multivariate receptor algorithms were applied to seven years of chemical speciation data to apportion fine particulate matter to various sources in Spokane, Washington. Source marker compounds were used to assess the associations between atmospheric concentration of these compounds and daily cardiac hospital admissions and/or respiratory emergency department visits. Total carbon and arsenic had high correlations with two different vegetative burning sources and were selected as vegetative burning markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In Phoenix, Arizona (Mar et al, 2006), wood combustion was associated with cardiovascular mortality, with effect estimates slightly lower than those for traffic particles. Finally, in Spokane, Washington (Schreuder et al, 2006), associations with cardiovascular mortality were of similar strength for biomass combustion and traffic. Only in a study conducted in Washington, DC (Ito et al, 2006), was no clear effect of particles from biomass combustion (or traffic) on cardiovascular health (mortality) observed.…”
Section: Epidemiological Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…In Phoenix, Arizona (Mar et al, 2006), wood combustion was associated with cardiovascular mortality, with effect estimates slightly lower than those for traffic particles. Finally, in Spokane, Washington (Schreuder et al, 2006), associations with cardiovascular mortality were of similar strength for biomass combustion and traffic. Only in a study conducted in Washington, DC (Ito et al, 2006), was no clear effect of particles from biomass combustion (or traffic) on cardiovascular health (mortality) observed.…”
Section: Epidemiological Studiesmentioning
confidence: 91%
“…In some studies, the source has been associated with cardiovascular (Andersen et al, 2007;Cakmak et al, 2009;Ito et al, 2006;Yue et al, 2007) or respiratory health (Cakmak et al, 2009;Gent et al, 2009). However, there are also studies without evidence of cardiovascular (Lanki et al, 2006;Mar et al, 2006) or respiratory effects (Jacquemin et al, 2009;Lall, Ito & Thurston, 2011;Schreuder et al, 2006). Only a few of these studies were published after 2009 -that is they have not affected the formulation of the integrated science assessment.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass burning can significantly affect global climate, regional air quality, visibility, ecosystems, and human health (e.g., Ramanathan et al, 2001;Seinfeld and Pandis, 2006). Residential heating with wood has been associated with adverse health effects (Boman et al, 2003;Naeher et al, 2007), and it has also been shown that biomass burning emissions contribute to respiratory hospitalizations (Schreuder et al, 2006). Quantification of biomass burning emissions is mandatory to understand the impact of this source on regional and local air quality.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have examined the impact on nearby local communities of exposures to wildfire aerosols. Associated health effects include increased emergency department visits and hospital admissions for chronic obstructive pulmonary disease (COPD), bronchitis, asthma and chest pain [7,13,15,[34][35][36][37]. For example, the San Diego wildfire in October 2003 caused the daily 24 h average PM 2.5 concentrations to exceed 150 µg/m 3 , and was associated with significant increases in hospital room emergency room visits for asthma, respiratory problems, eye irritation, and smoke inhalation [38], and increased eye and respiratory symptoms, medication use and physician visits in children living in the San Diego area [30].…”
Section: Introductionmentioning
confidence: 99%